Implementation of ant colony system for DNA sequence optimization - Ibrahim, Zuwairie (ISAROB, 2009)
DNA computation as a new paradigm has the computational power of molecules for information processing and many computational models have been proposed for solving mathematical problems in laboratory experiments. In order to achieve the correct computation, a set good of DNA sequences is crucial, because the code determines the way to process information on sequences in the experiments. Much works have focused on designing the DNA sequences to archive a reliable molecular computation and many algorithms have been proposed to obtain a set of good DNA sequences. In this paper, Ant Colony System (ACS) is proposed to solve the DNA sequence design problem. ACS used some ants to get their solutions based on the pheromone in their colony. A model is prepared which consists of four nodes representing four DNA bases. The results of the proposed approach are compared with the other methods such as Genetic Algorithm.